IMPLEMENTATION OF MARKETING MIX IN SUBSIDIED HOUSING IN ISLAMIC ECONOMIC PERSPECTIVE - Hidayanti, Nur Fitri (Journal of Sharia Economy and Islamic Tourism, 2020)
The need for housing in the city of Mataram is getting higher every year. Unfortunately, this need is not supported by the appropriate purchasing power. Therefore, the government launched a subsidized KPR with affordable down payments and installments. One of the private companies that participate in developing subsidized housing is PT. Citra Jaya Graha. The marketing system carried out by PT. Citra Jaya Graha in selling its products uses a marketing mix system or better known as a marketing mix. First, PT. Citra Jaya Graha in providing its production in the form of subsidized housing, prioritizes quality by providing facilities and infrastructure. Second, in setting the price, PT Citra Jaya Graha implements a subsidized house selling price limit that has been stipulated in Kepmenpupr number 552 / kpts / m / 2016 concerning the income limit for the target group of subsidized houses, the limit on the selling price of a prosperous house. Third, PT. Citra Jaya Graha in promoting its products uses billboards, brochures, and employees (marketing), printed media (Lombok Pos newspaper) and electronic media such as websites and Facebook. Fourth, the process of distributing BTN houses is carried out directly, marketing offers directly to prospective buyers. PT. Citra Jaya Graha is also building an Islamic housing complex. For example, the Griya Assamiq housing which is intended specifically for Muslim consumers and the construction of prayer rooms or mosques in several housing complexes that he has built. Kebutuhan rumah di kota Mataram semakin tahun semakin tinggi. Sayangnya kebutuhan tersebut tidak didukung dengan kemampuan beli yang sesuai. Oleh sebab itu, pemerintah meluncurkan KPR bersubsidi dengan uang muka dan cicilan yang terjangkau. Salah satu perusahan swasta yang berpartisipasi dalam megembangkat perumahan bersubsidi ialah PT. Citra Jaya Graha. Sistem pemasaran yang dilakukan oleh PT. Citra Jaya Graha dalam menjual hasil produksinya menggunakan sistem bauran pemasaran atau lebih dikenal dengan marketing mix. Pertama, PT. Citra Jaya Graha dalam menyedikan hasil produksinya yang berupa perumah subsidi mengutamakan kualitas dengan menyedikan sarana dan prasarana. Kedua, dalam menetapkan harga PT.Citra Jaya Graha melakukan batasan harga jual rumah subsidi yang telah ditetapkan dalam kepmenpupr nomor 552/kpts/m/2016 tentang batasan penghasilan kelompok sasaran rumah bersubsidi, batasan harga jual rumah sejahtera. Ketiga, PT. Citra Jaya Graha dalam mempromosikan produk yang di hasilkan menggunakan media baliho, brosur, dan karyawan (marketing), media cetak (surat kabar Lombok Pos) dan media elektronik seperti website dan facebook. Keempat, proses pendistribusian rumah BTN dilakukan secara langsung, marketing menawarkan secara langsung kepada calon pembeli. PT. Citra Jaya Graha juga membangun kompleks perumahan yang islami. Seperti, perumahan Griya Assamiq yang diperuntuhkan khusus untuk konsumen yang beragama muslim dan di dirikannya musholla atau masjid di beberapa kompleks perumahan yang telah dibangunnya.